1990
DOI: 10.1007/bf01140573
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial interactions with silver

Abstract: This review examines interactions between bacteria and the biologically non-essential metal, silver. Aspects of silver toxicity, tolerance and accumulation (possible binding and uptake as opposed to energy-dependent transport) in bacteria are discussed. In addition, plasmid biology is examined briefly since little information is available on the exact mechanism(s) of plasmid-endoced silver resistance in bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 24 publications
0
80
0
2
Order By: Relevance
“…Although not investigated in this study, these antibacterial and bactericidal behaviors of Ag ions may result from the following mechanisms: inhibition of DNA replication and mitosis, effects of the permeability of the cell membrane, and control of the oxidation of glucose as reported by other researchers 26) . The antibacterial and bactericidal effects of the Ag ion-coated wires were confirmed in measuring waterinsoluble glucan (WIG), the main component of biofilm formed by cariogenic bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…Although not investigated in this study, these antibacterial and bactericidal behaviors of Ag ions may result from the following mechanisms: inhibition of DNA replication and mitosis, effects of the permeability of the cell membrane, and control of the oxidation of glucose as reported by other researchers 26) . The antibacterial and bactericidal effects of the Ag ion-coated wires were confirmed in measuring waterinsoluble glucan (WIG), the main component of biofilm formed by cariogenic bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…24 Thus, it is likely that the mechanisms of AgNP toxicity are similar to those for copper toxicity. Slawson et al 25 reported that Ag + toxicity was reduced when Cu 2+ is also present, indicating that silver may compete with copper for entry into the cell. There appears to be some promiscuity of bacterial metal transport proteins, the functions of which have not been fully elucidated.…”
Section: Disruption Of Oxidative Balancementioning
confidence: 99%
“…Although the efforts directed towards the biosynthesis of nanomaterials are recent, the interactions between micro-organisms and metals have been well documented (11)(12)(13)(14) and the ability of micro-organisms to extract and/or accumulate metals is employed in commercial biotechnological processes such as bioleaching and bioremediation.…”
Section: Introductionmentioning
confidence: 99%